Ultrasensitive Pressure Detection of Few‐Layer MoS2. Issue 4 (17th October 2016) - Yu, Feifan; Liu, Qianwen; Gan, Xin; Hu, Mingxiang; Zhang, Tianyi; Li, Cheng; Kang, Feiyu; Terrones, Mauricio; Lv, Ruitao
Abstract : Ultrasensitive pressure sensors are constructed with few‐layer MoS2 films. As‐designed Fabry–Perot (F–P) sensors exhibit nearly synchronous pressure–deflection responses with a very high sensitivity (89.3 nm Pa −1 ), which is three orders of magnitude higher than those of conventional diaphragm materials (e.g., silica, silver films). This kind of F–P sensor may open up new avenues for 2D materials in biomedical and environmental applications.